Production of gymnemic acid depends on medium, explants, pgrs, color lights, temperature, photoperiod, and sucrose sources in batch culture of gymnema sylvestre - Ahmed, A.B.; Rao, A.S.; Rao, M.V.; Taha, R.M. (Hindawi Publishing Corporation, 2012)
Gymnema sylvestre (R.Br.) is an important diabetic medicinal plant which yields pharmaceutically active compounds called gymnemic acid (GA). The present study describes callus induction and the subsequent batch culture optimization and GA quantification determined by linearity, precision, accuracy, and recovery. Best callus induction of GA was noticed in MS medium combined with 2,4-D (1.5 mg/L) and KN (0.5 mg/L). Evaluation and isolation of GA from the calluses derived from different plant parts, namely, leaf, stem and petioles have been done in the present case for the first time. Factors such as light, temperature, sucrose, and photoperiod were studied to observe their effect on GA production. Temperature conditions completely inhibited GA production. Out of the different sucrose concentrations tested, the highest yield (35.4 mg/g d.w) was found at 5% sucrose followed by 12 h photoperiod (26.86 mg/g d.w). Maximum GA production (58.28 mg/g d.w) was observed in blue light. The results showed that physical and chemical factors greatly influence the production of GA in callus cultures of G. sylvestre. The factors optimized for in vitro production of GA during the present study can successfully be employed for their large-scale production in bioreactors.